Teacher-Parent Collaboration in Developing Independence and Social-Emotional Competencies: A Qualitative Case Study in Indonesian Elementary Education - Listianti, Listianti; Sauri, R Supyan (Journal of Innovation and Research in Primary Education, 2026)
The development of independence and social-emotional competencies in elementary students requires systematic collaboration between teachers and parents, yet structured partnership models remain insufficiently explored in Indonesian educational contexts. This study examines teacher-parent collaboration in developing students’ independence and social-emotional skills at SDN 011 Cibuntu, Bandung City, identifying critical components and implementation mechanisms. A qualitative case study design was employed, collecting data through in-depth interviews with five teachers, one school principal, and eight parents, supplemented by systematic observation and document analysis. Data were analyzed using inductive thematic analysis following Braun and Clarke’s framework. Three essential collaboration dimensions emerged: joint planning incorporating bidirectional input, coordinated implementation through aligned home-school strategies and intensive communication (averaging 3.7 exchanges per parent monthly), and collaborative evaluation enabling dual-context monitoring. Active collaboration improved student independence indicators and social-emotional competencies, though implementation faced substantial barriers including documentation gaps, time constraints affecting economically disadvantaged families, and informal evaluation practices. Social-emotional development required more intensive collaboration than independence skills, revealing differential impacts across developmental domains. Systematic teacher-parent collaboration effectively supports student development when accompanied by structured protocols, professional development, flexible engagement options, and formal evaluation tools. Realizing collaboration potential demands systemic supports addressing capacity building at individual, institutional, and policy levels rather than relying on individual initiative alone.